Essential cooperation of N-cadherin and neuroligin-1 in the transsynaptic control of vesicle accumulation - Stan, Adriana; Pielarski, K. N.; Brigadski, T.; Wittenmayer, Nina; Fedorchenko, O.; Gohla, A.; Lessmann, V.; Dresbach, Thomas; Gottmann, K. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cell adhesion molecules are key players in transsynaptic communication, precisely coordinating presynaptic differentiation with postsynaptic specialization. At glutamatergic synapses, their retrograde signaling has been proposed to control presynaptic vesicle clustering at active zones. However, how the different types of cell adhesion molecules act together during this decisive step of synapse maturation is largely unexplored. Using a knockout approach, we show that two synaptic adhesion systems, N-cadherin and neuroligin-1, cooperate to control vesicle clustering at nascent synapses. Live cell imaging and fluorescence recovery after photobleaching experiments at individual synaptic boutons revealed a strong impairment of vesicle accumulation in the absence of N-cadherin, whereas the formation of active zones was largely unaffected. Strikingly, also the clustering of synaptic vesicles triggered by neuroligin-1 overexpression required the presence of N-cadherin in cultured neurons. Mechanistically, we found that N-cadherin acts by postsynaptically accumulating neuroligin-1 and activating its function via the scaffolding molecule S-SCAM, leading, in turn, to presynaptic vesicle clustering. A similar cooperation of N-cadherin and neuroligin-1 was observed in immature CA3 pyramidal neurons in an organotypic hippocampal network. Moreover, at mature synapses, N-cadherin was required for the increase in release probability and miniature EPSC frequency induced by expressed neuroligin-1. This cooperation of two cell adhesion systems provides a mechanism for coupling bidirectional synapse maturation mediated by neuroligin-1 to cell type recognition processes mediated by classical cadherins.
Gesehen am 20.10.2023